Trends in American female youth and junior weightlifting performance from 2015 to 2023 - Healis, J.; Adams, K. J.; Lawrence, M. M. (The Journal of Strength and Conditioning Research, 2026)
This investigation assessed performance trajectories of American Youth and Junior female weightlifters in the snatch (SNT), clean and jerk (CJ), and total (T) from 2015 to 2023, using results from sanctioned USA Weightlifting events. Subjects (N = 960-2,245) were =20 years old at initial competition. Performance was evaluated using strength-to-mass (SM) ratios, tracking the highest SM ratios, and allometric scaling in 3-month timeframes using each athlete's best total per timeframe for the first 3 years and 6-month timeframes over the study period (~9 years). Performance was analyzed using percentage changes and Cohen's d effect sizes (ES). For 3-month timeframes, the largest initial improvements were between 3 and 6 months for the SNT (12.44%; ES = 0.00), CJ (11.12%; ES = -0.01), and T (11.50%; ES = 0.00). For 6-month timeframes, large improvements occurred from 6 to 12 months for SNT (SM = 0.80 ± 0.20 kg, 14.91%, ES = 0.11), CJ (SM = 1.03 ± 0.25 kg, 13.34%, ES = 0.10), and T (SM = 1.82 ± 0.45 kg, 13.87%, ES = 0.11) with potential performance plateaus observed around year 7 (78-84 months) for SNT (-0.25%, ES = 0.04), CJ (-2.68%, ES = 0.07), T (-1.90%, ES = 0.07). Allometric results supported these trends, showing similar peak timing and magnitude. Reduced participation rates from the first 3/6-month timeframes (N = 2,245) to the next 6/12-month timeframes (N = 970-1,209) continued until the final timeframe, which cannot be strictly attributed to aging out. Compared with data before 2015, weightlifters had higher initial performances, greater early gains, and potentially earlier plateaus. This suggests that evolving coaching methods improved performance, but targeted strategies are needed to sustain engagement and overcome plateaus in later training stages.